Luminescence properties and energy transfer of the near-infrared phosphor Ca3In2Ge3O12:Cr3+, Nd3+. Issue 44 (5th October 2022) - Wang, Tao; Cao, Lingwei; Wang, Zhijun; Li, Panlai
Abstract : Improvement of the luminescence properties of Ca3 In2 Ge3 O12 :Cr 3+, Nd 3+ via energy transfer and its potential application in silicon solar cells. Abstract : The double doping strategy based on energy transfer is an effective way to regulate the NIR spectral distribution. In this work, Ca3 In2 Ge3 O12 : x Nd 3+ (CIG: x Nd 3+ ) and Ca3− x In1.93 Ge3 O12 :0.07Cr 3+, y Nd 3+ (CIG:0.07Cr 3+, y Nd 3+ ) phosphors are successfully prepared via a high-temperature solid-state method. CIG:0.07Cr 3+ shows broadband emission centered at 804 nm, which covers most of the excitation peaks of Nd 3+ ions. Under excitation at 480 nm, Cr 3+ can provide effective energy transfer to Nd 3+ . In addition, CIG:0.07Cr 3+, 0.15Nd 3+ has good temperature stability, and maintains 68.98% of the room-temperature intensity at 150 °C. The phosphors can convert short-wave photons to long-wave photons and enhance solar cell utilization, demonstrating the potential application of this material in solar spectral conversion technology.